Influence of ocean acidification on elemental mass balances and particulate organic matter stoichiometry in natural plankton communities - Boxhammer, Tim (2018)
The oceanic uptake of anthropogenic CO2 leads to a gradual acidification of the ocean. Ocean acidification (OA) is known to affect marine biota from the organism to the ecosystem level but with largely unknown consequences for the cycling of key elements such as carbon, nitrogen, and phosphorus. However, the ocean’s ability to absorb anthropogenic carbon or to provide sufficient food for humankind depends on these oceanic material cycles. This doctoral dissertation thus aimed to assess the influence of OA on biogeochemical cycles of elements in natural pelagic food webs of several trophic levels (up to fish larvae) over extended time scales of weeks to months. Large-scale pelagic mesocosms (up to 75 m3 per unit) were deployed in different marine ecosystems and new methods were developed to quantify the downward flux of particulate organic matter under simulated OA. This thesis reports on the potential influence of OA on element pool partitioning and particulate organic matter stoichiometry with consequences for biogeochemical cycling of elements in the ocean. Furthermore the potential and limitations of biogeochemical measurements inside pelagic mesocosms that host entire plankton communities are elucidated.